2005
DOI: 10.1203/01.pdr.0000147568.14392.f0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Reduced Apoptosis in Neonatal Neutrophils

Abstract: Apoptosis, which leads to phagocytosis by mononuclear cells, represents the primary mechanism for removing neutrophils from inflamed tissues and minimizing injury. The present studies show that membrane phosphatidylserine turnover and permeability, as well as DNA fragmentation, were reduced in neutrophils from neonates when compared with adults. The activity of caspase 3 and expression of the proapoptotic proteins Bax, Bad, and Bak were also decreased in neonatal relative to adult neutrophils. These findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 42 publications
8
44
1
1
Order By: Relevance
“…1). In both neonatal cell populations, apoptosis was significantly reduced when compared with adult cells, which is consistent with previous reports (1,2,14). In further studies, we analyzed potential mechanisms underlying the inhibitory effects of labor on neonatal neutrophil apoptosis.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1). In both neonatal cell populations, apoptosis was significantly reduced when compared with adult cells, which is consistent with previous reports (1,2,14). In further studies, we analyzed potential mechanisms underlying the inhibitory effects of labor on neonatal neutrophil apoptosis.…”
Section: Resultssupporting
confidence: 88%
“…The rate of apoptosis is related to the activity of these effector pathways, which induce cell and nuclear membrane permeability (13). Consistent with previous findings (2,14), we found that apoptosis is impaired in neonatal neutrophils relative to adult cells and that this is associated with reduced caspase-3 activity in neonatal cells. Interestingly, labor had no effect on caspase-3 activity or on expression of IAP-2, an intracellular protein induced by inflammatory stimuli and hypoxia that inhibits caspase activity (20).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, compared to adults, the markers of apoptosis such as caspase 3 activity, histone-associated DNA fragments and strand breaks are reduced in neonatal neutrophils. The proapoptotic Bcl-2-family proteins are also decreased in the neutrophils of a newborn relative to adult cells [77]. These features mean that programmed cell death is impaired.…”
Section: Characteristics Of Neutrophil Apoptosis In Infants and Newbornsmentioning
confidence: 99%
“…Thus, the delayed programmed death of these cells contributes to the pathogenesis of respiratory distress-syndrom, bronchopulmonary dysplasia and necrotizing enterocolitis, improving the resolution of an inflammatory response, prolonging tissue injury and causing the acute course of the disease [77,78].…”
Section: Characteristics Of Neutrophil Apoptosis In Infants and Newbornsmentioning
confidence: 99%